Mekanisme Pendistribusian Liquefied Petroleum Gas (LPG) Dalam Konsep Ibnu Kholdun - Bagus Rohmatulloh (Pendidikan Agama Islam STAIPI Persis Bandung, 2022)
One of product becoming social needs is LPG, and then LPG distribution should be done well for creating a social prosperity. Same as Ibn Khaldun concept about distribution that is always attachable with the price of the product because the price influences the distribution. Thus, the price of product consists of three elements. They are salary, profit and tax. If the distributor doesn’t run the three elements well, then there will not be smooth social prosperity. This research used library research and documenter study for getting data. It’s being analyzed with descriptive method. From analysis is known that there were problems in LPG distribution impacting to the high price, late delivery, less LPG capacity, and there isn’t prosperity. They need the fast solution for measuring these problems.